Rediscutindo os grupos funcionais alimentares em macroinvertebrados de riachos de Mata Atlântica - Venuso, Laura Joia (Universidade Federal de São Carlos, 2025)
Functional Feeding Groups are used to describe the ecological role of aquatic macroinvertebrates in lotic ecosystems, associating them with feeding acquisition strategies and types of consumed resources. This classification, although relevant and extremely important for understanding aquatic trophic relationships, presents certain limitations by assuming fixed diets for these organisms. This study aimed to revisit the applicability of FFGs as dietary predictors, based on stomach content analysis of 17 taxa collected from streams in Parque Estadual Intervales. Additionally, the relationship between individual biomass increase and consumption of animal tissue was evaluated as a possible indicator of trophic changes associated with growth. The results revealed a wide diversity in dietary contents among groups, including the presence of animal tissue even among taxa traditionally considered non-predatory, such as filtering-collectors and shredders. Furthermore, a general positive trend was identified between increased biomass and carnivory, although statistically significant only for four taxa — two predators and two filtering-collectors. This pattern suggests that body growth may broaden the dietary spectrum of certain organisms, influencing their trophic position. In other words, the trophic position of an individual is not necessarily static and may vary over time in response to ontogenetic and contextual factors. These findings contribute to refining the FFG concept, highlighting the importance of interpreting them as generalized functional strategies rather than rigid descriptors of dietary niche.
Redescussing functional feeding groups in macroinvertebrates from Atlantic Forest streams
Keywords: Insetos aquáticos; Conteúdo estomacal; Riachos tropicais; Carnivoria; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS